Crown Fossils - Frédéric Bigras-Burrogano; Jordan B. Kinder (Museum & Society)
This article explores how artists, by adopting the posture of an artist-museologist, can propose new understandings between museums, their collections, broader perceptions of knowledge, and the power of choosing what constitutes the museum through a critical-historical account of the Royal Tyrrell Museum’s historical and ongoing relationship to resource extraction and Indigenous land dispossession. We define the term artist-as-museologist as an artist who is concerned with borrowing, addressing, infiltrating, or operating through museum collections, their scenography, or dissemination activities. Applying institutional critique to the museum, we show how artistic practice can help to excavate buried power relations that condition the extractive museum, like the Royal Tyrrell, named after geologist, Joseph Burr Tyrrell, who discovered the Albertasaurus during an expedition of the Geological Survey of Canada.